Becoming a U.S. Citizen Lessons on Naturalization - Heiserman, Robert G.; American Newspaper Publishers Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This unit, through a series of learning activities, is designed to give students a sense of what it means to seek U.S. citizenship. The first activity is created to help students understand the Naturalization Examination process by role-playing the examination and through creating their own examination for citizenship. The Oath of United States Citizenship is studied through group discussions of citizenship requirements and a discussion of the commitment inherent in citizenship. The Immigration and Naturalization Service (INS) criteria for citizenship are explored by presenting students with various law-related situations and having them decide if an individual qualifies for citizenship. A follow-up activity is designed for study of the 1986 legislation that allowed illegal immigrants who have been in the United States since 1982 to become citizens. (SM)
Teachers.
Students.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizen Role; Citizenship; Citizenship Education; Citizenship Responsibility; Civics; Immigrants; Instructional Materials; Law Related Education; Learning Activities; Learning Modules; Secondary Education; Social Studies; United States Government (Course); United States History; Immigration and Naturalization Service; Naturalization Programs; Guides, Classroom -- Learner; Guides, Classroom -- Teacher